2015
DOI: 10.1016/j.jcrysgro.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the crystalline quality of AlN layer grown on sapphire substrates by metalorganic chemical vapor deposition

Abstract: a b s t r a c tWe studied temperature dependence of crystalline quality of AlN layers at 1050-1250 1C with a fine increment step of around 18 1C. The AlN layers were grown on c-plane sapphire substrates by metalorganic chemical vapor deposition (MOCVD) and characterized by X-ray diffraction (XRD) ω-scans and atomic force microscopy (AFM). At 1050-1068 1C, the templates exhibited poor quality with surface pits and higher XRD (002) and (102) full-width at half-maximum (FWHM) because of insufficient Al atom mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 28 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…3(f), where the surface is close to full coalescence at a thickness of $1.40 mm, indicating the relation between dislocation and uncoalescence. Okada et al have shown that the slower annihilation of dislocations led to a reduction in the biaxial strain, dislocation density, and cracks [13], which can be used to explain the relatively low dislocation density obtained in this study, in addition to the reduced thermal stress at lower temperatures [23]. Therefore, the slower annihilation of dislocations was caused by a long transition from 3D to 2D growth modes due to a lower Al-atom mobility as compared to the ones at higher temperatures.…”
Section: Nmmentioning
confidence: 72%
See 1 more Smart Citation
“…3(f), where the surface is close to full coalescence at a thickness of $1.40 mm, indicating the relation between dislocation and uncoalescence. Okada et al have shown that the slower annihilation of dislocations led to a reduction in the biaxial strain, dislocation density, and cracks [13], which can be used to explain the relatively low dislocation density obtained in this study, in addition to the reduced thermal stress at lower temperatures [23]. Therefore, the slower annihilation of dislocations was caused by a long transition from 3D to 2D growth modes due to a lower Al-atom mobility as compared to the ones at higher temperatures.…”
Section: Nmmentioning
confidence: 72%
“…Thus there have been few successful studies of growing highquality planar AlN layers on the sapphire substrates below 1200 8C. Recently, a detailed temperature dependence study indicated that the Al atom mobility was adequate to achieve coalesced and smooth surface at temperatures as low as 1086 8C without the use of ELO or PALE [23]. Hence the planar AlN layers with high quality may be obtainable at such temperatures.…”
mentioning
confidence: 99%
“…Compared with the indium and gallium atoms, aluminum atoms have a lower surface mobility during migration. [18][19][20][21][22] The growth temperature for AlGaN QBs in our samples has been reduced to 940°C to suppress the expected thermal damage to InGaN QWs. At the same time, the growth rate of the AlGaN layer was also reduced to a value as low as 0.012 nm/s to improve the surface morphology under this low temperature.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] These studies indicate that in spite of lattice and thermal mismatch, it is possible to obtain high internal quantum efficiency (IQE) and thus high material gain to achieve low-threshold lasing by reducing the dislocation density in III-nitride AlGaN heterostructures to a relatively low level. 15,16 In comparison to the edge-emitting lasers, verticalcavity surface-emitting lasers (VCSELs) possess advantageous characteristics including high-speed modulation, good beam quality, and control of production process. Despite decent progress of edge-emitting DUV lasers, little has been reported for the development of DUV VCSELs.…”
Section: Onset Of Surface Stimulated Emission At 260 Nm From Algan Mumentioning
confidence: 99%